Fulminant myocarditis, severe pediatric acute respiratory distress syndrome associated with H1N1 influenza and enteric fever rescued by prone ventilation: A case Report - Goutam Goswami; Pradeep Kumar Sharma; Nikhil Vinayak (Wolters Kluwer Medknow Publications, 2021)
H1N1 influenza-associated fulminant myocarditis with pediatric acute respiratory distress syndrome (PARDS) is rare. We report a child of fulminant myocarditis, severe PARDS associated with H1N1 and enteric fever. She rapidly developed severe PARDS and refractory hypoxemia. She was successfully rescued with prone ventilation. Fulminant myocarditis with PARDS can be a manifestation of H1N1 infection. These scenarios pose a tough challenge, especially in resource-limited settings. Although we successfully managed our patient with prone ventilation, success in one case cannot be generalized until more evidence is generated.